MAYOR MENÉNDEZ, Pablo y AREILZA CARVAJAL, José M. (2002). Internet, una profecía. Barcelona: Editorial Ariel (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2002)
Recensión de la obra: MAYOR MENÉNDEZ, Pablo y AREILZA CARVAJAL, José M. (2002). Internet, una profecía. Barcelona: Editorial Ariel.